2002
DOI: 10.1182/blood.v100.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new subpopulation of mouse CD8α+ B220+ dendritic cells endowed with type 1 interferon production capacity and tolerogenic potential

Abstract: We describe a new B220 ؉ subpopulation of immaturelike dendritic cells (B220 ؉ DCs) with low levels of expression of major histocompatibility complex (MHC) and costimulatory molecules and markedly reduced T-cell stimulatory potential, located in the thymus, bone marrow, spleen, and lymph nodes. B220 ؉ DCs display ultrastructural characteristics resembling those of human plasmacytoid cells and accordingly produce interferon-␣ after virus stimulation. B220 ؉ DCs acquired a strong antigen-presenting cell capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
154
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(168 citation statements)
references
References 37 publications
(41 reference statements)
13
154
0
Order By: Relevance
“…An additional cell population has recently been identified that stains with both Ly-6C and Ly-6G mAbs (12,13). These cells, termed plasmacytoid dendritic cells, comprise a rare population found in many hematopoietic tissues, including spleen and lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional cell population has recently been identified that stains with both Ly-6C and Ly-6G mAbs (12,13). These cells, termed plasmacytoid dendritic cells, comprise a rare population found in many hematopoietic tissues, including spleen and lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression has been studied primarily using the monoclonal antibody (mAb) RB6-8C5 (anti Gr-1), but other monoclonal antibodies (mAbs) have also been developed against this antigen (Ag), including NIMPR-14 (9). Expression of Ly-6G has also recently been described on plasmacytoid dendritic cells (12,13).…”
mentioning
confidence: 99%
“…Immature plasmacytoid DC (pDC) have recently been identified in the spleen, lymph node and bone marrow and have been shown to have the capacity either to induce tolerance in the steady state or to produce IFN-␣ upon CpG or viral stimulation (16). Therefore, we wanted to know whether these cells were also present in the liver.…”
Section: Liver DC Are Comprised Of Multiple Subtypes With Heterogeneomentioning
confidence: 99%
“…After this characterization in human, its murine PDC counterpart was then isolated 1619 . Human PDC are usually identified as CD4 + , CD303 + (previously known as BDCA-2), and CD123 high , whereas mouse PDC are CD11c int , B220 + , SIGLEC-H + , and CD317 + 7 .…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…Receptors expressed by PDC, such as immunoglobulin-like transcript 7 61 or CD303 62 may also inhibit TLR7/9-mediated type I IFN production. In addition, PDC can produce, under certain circumstances, high levels of immunosuppressive cytokines, such as IL-10 19, 25 or TGF-β 56, 63 . In addition, PDC participate in the maintenance of immune tolerance via the induction and/or expansion of regulatory T cells (please refer to Refs# 7, 63 ; this is out of the scope of this review).…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%